Maslahah sebagai Landasan Transformasi Undang-Undang Wakaf di Indonesia: Analisis Filosofis terhadap Kesejahteraan Sosial - Dadi Wardiman; Nurrohman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the application of the maslahah principle in the transformation of waqf law in Indonesia and its impact on social welfare. the importance of effective and sustainable waqf management to improve the quality of life of the community. The research method used is a qualitative approach with normative analysis, which examines the regulations and practices of waqf management in Indonesia. The research results show that the maslahah principle is applied in the transformation of waqf law in Indonesia through integration with various policies and regulations governing the management of waqf assets. Law Number 41 of 2004 concerning Waqf has integrated the principle of maslahah by determining that the management of waqf assets must be carried out in the public interest and can provide maximum benefits for the community. The impact of the maslahah philosophy on social welfare in the context of waqf is very significant, where the application of this principle has increased the effectiveness and efficiency of waqf asset management, so that it can be used for various social programs such as education, health and social infrastructure. Real examples such as productive waqf management, istibdal of waqf assets, and the formation of the Indonesian Waqf Board (BWI) show how the principle of maslahah can directly improve community welfare.